Child Rights Fulfilment in Families Practicing Early Marriage: A Juridical-Empirical Analysis of Child Protection Law Implementation in Blangkejeren, Gayo Lues Regency - Mala Hayati; Fakhrurrazi M. Yunus; Gamal Achyar (An-Nisa: Journal of Islamic Family Law, 2025)
The phenomenon of Early marriage remains a critical social issue in Blangkejeren District, Gayo Lues Regency, with significant implications for the fulfilment of children’s rights within the family. Despite the existence of a comprehensive legal framework, particularly Law Number 35 of 2014 on Child Protection, its implementation at the family level among early-married couples remains ineffective. This study examines the fulfilment of children’s rights in families practising early marriage and identifies the legal and socio-familial factors hindering its realisation. Employing a juridical-empirical approach with a qualitative descriptive design, the research integrates normative legal analysis with empirical data collected through in-depth interviews with early-married families, community leaders, and relevant institutions. The findings reveal a clear gap between legal norms and social practice, as children’s rights related to caregiving, education, and health are inadequately fulfilled. These conditions are driven by parents’ economic and psychological unpreparedness, limited legal awareness, and weak institutional support. The study highlights the need to strengthen child protection law implementation through structured premarital education, young family empowerment, and enhanced institutional oversight.